2005
DOI: 10.1002/app.21576
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cellulose fiber with silk sericin

Abstract: Cellulose fiber surface was modified with silk sericin (or simply, sericin). Sericin fixation on cellulose was confirmed by environmental scanning electron microscopy (ESEM) and Fourier transform infrared spectrophotometry-attenuated total reflectance (FTIR-ATR). Sericin content in finished samples was estimated by dyeing treated fabrics with an acid dye, Supranol Bordeaux B, and determining K/S and L values of the dyed fabrics. The treated fabrics were tested for free formaldehyde content, crease recovery, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 11 publications
3
30
0
2
Order By: Relevance
“…[20][21][22] Generally, hydrophobic surfaces are considered to be more protein-absorbent than hydrophilic ones, due to the strong hydrophobic interactions. 9,23 However, this could cause conformational changes or, sometimes, denaturation of proteins and, thus, lower the proliferation of cells on such surfaces. It is reported that biomaterial surfaces with moderate hydrophilicity display improved cell growth and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Generally, hydrophobic surfaces are considered to be more protein-absorbent than hydrophilic ones, due to the strong hydrophobic interactions. 9,23 However, this could cause conformational changes or, sometimes, denaturation of proteins and, thus, lower the proliferation of cells on such surfaces. It is reported that biomaterial surfaces with moderate hydrophilicity display improved cell growth and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Esse descarte pode provocar danos ao meio ambiente, que seriam evitados se a proteína fosse reaproveitada, pois esta possui várias propriedades que vêm despertando o interesse da comunidade científica, como aplicação em cosméticos, suportes para enzimas imobilizadas, suplementação alimentar, materiais médicos e farmacêuticos e fibras funcionais, bem como características antioxidantes, antibacterianas e resistência à radiação ultravioleta (ZHANG, 2002;KONGDEE et al, 2004;MONDAL et a., 2007; ARANWIT et al, 2012).…”
Section: Introductionunclassified
“…Hoje, é utilizada em diversas aplicações como cosméticos, membranas, suportes para enzimas imobilizadas, suplemento alimentar, matéria-prima para medicamentos, e fibras funcionais (Kongdee et al, 2004).…”
Section: Introductionunclassified